Cesarean Scar Ectopic Pregnancy: Current Management Strategies. Issue 5 (May 2018) - Glenn, Tanya L.; Bembry, James; Findley, Austin D.; Yaklic, Jerome L.; Bhagavath, Bala; Gagneux, Pascal; Lindheim, Steven R.
Abstract : Importance: Cesarean scar ectopic pregnancy (CSEP) has a high rate of morbidity with nonspecific signs and symptoms making identification difficult. The criterion-standard treatment of CSEP has been subject to debate. Objective: This review defines CSEP, discusses pathogenesis and diagnosis, and compares treatment options and outcomes. Evidence Acquisition: A literature review was performed utilizing the term cesarean scar ectopic pregnancy and subsequently selecting only meta-analyses and systematic reviews. Only articles published in English were included. Relevant articles within the reviews were analyzed as necessary. Results: Five basic pathways have been identified in treatment of CSEP: expectant management, medical therapy, surgical intervention, uterine artery embolization, or a combination approach. Expectant management has the highest probability of morbid outcomes, including hemorrhage, uterine rupture, and preterm delivery. Medical management often requires further treatment with additional medication or surgery. Different surgical methods have been explored including uterine artery embolization; dilation and curettage; surgical removal via vaginal, laparoscopic, or laparotomic approach; and hysterectomy. Each method has various levels of success and depends on surgeon skill and patient presentation. Conclusions: Recent research supports any method that removes the pregnancy and scar to reduce morbidity and promote future fertility. Laparoscopic and transvaginal approaches are options for CSEP treatment, although continued research is required to identify the optimal approach. Relevance: As cesarean delivery numbers rise, a subsequent increase in CSEPs can be anticipated. The ability to accurately diagnose and treat this morbid condition is vital to the practice of any specialist in general obstetrics and gynecology. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to delineate the signs and symptoms of cesarean scar ectopic pregnancy (CSEP), recall the ultrasound findings that are diagnostic for CSEP, list common complications, and discuss the relative effectiveness management options for CSEP.